Primary care management of non-institutionalized elderly diabetic patients: The S.AGES cohort – Baseline data. Issue 4 (August 2015) - Bucher, Sophie; Bauduceau, Bernard; Benattar-Zibi, Linda; Bertin, Philippe; Berrut, Gilles; Corruble, Emmanuelle; Danchin, Nicolas; Delespierre, Tiba; Derumeaux, Geneviève; Doucet, Jean; Falissard, Bruno; Forette, Francoise; et al.
Highlights Patients (983 diabetics) were included by 213 primary care providers. S.AGES patients were generally healthy with well-controlled diabetes. The results were consistent with others French and North American cohorts. The results showed increased complications with age, disease duration and severity. And showed increased use of insulin with age, disease duration and severity.